The Influence Of Promag's Marketing Mix And Its Impact On Customer Satisfaction Through The Creation Of Brand Equity - Siti Mulyati; MGS Aritonang; Iha Haryani Hatta (Jurnal Ekonomi, 2024)
This study aims to analyze the influence of the marketing mix, consisting of product, price, place, and promotion, on consumer satisfaction through the creation of brand equity in Promag products. The research adopts a quantitative approach with a descriptive design, involving 220 respondents selected through random sampling at several pharmacies in Tangerang Regency. Data were collected using structured questionnaires and analyzed using the Structural Equation Modeling (SEM) method. The results indicate that the elements of the marketing mix have varying effects on consumer satisfaction and brand equity. Product, price, and promotion variables show a negative influence on consumer satisfaction, while the place variable has a positive impact. On the other hand, product, price, and promotion positively contribute to building brand equity. These findings suggest that appropriate marketing strategies for the elements of the marketing mix can enhance Promag's brand equity; however, attention must be paid to their impact on consumer satisfaction to achieve optimal outcomes.